Successful treatment with dabigatran for consumptive coagulopathy associated with extensive vascular malformations. Issue 8 (December 2017) - Yasumoto, Atsushi; Ishiura, Ryohei; Narushima, Mitsunaga; Yatomi, Yutaka
Abstract : N/A: Vascular malformation is occasionally complicated by consumptive coagulopathy, known as localized intravascular coagulopathy (LIC), which is characterized by a reduced fibrinogen level, an elevated D-dimer level and a normal platelet count. We report the case of a 17-year-old Japanese girl who presented with LIC secondary to extensive vascular malformations, whose condition had progressed to disseminated intravascular coagulation (DIC). She suddenly presented with severe anaemia, despite the absence of obvious bleeding, and she began to require regular red blood cell (RBC) transfusions. As she was suffering from paroxysmal atrial fibrillation, we treated her with dabigatran, after obtaining informed consent. Immediately after the administration of dabigatran, the results of clotting tests improved dramatically. Seven months later, she has not required any RBC transfusions, and the dabigatran treatment has been well tolerated. The present case report suggests that dabigatran may be a useful treatment option for patients with DIC associated with vascular malformations.